Representation of Woman in the “Film Marlina: si Pembunuh dalam Empat Babak” - Retno Angraeni S; Citra Buana Halil (Universitas Cenderawasih, 2025)
In the modern era, opportunities for women and men should be equal. However, this is still far from the reality faced by women in rural areas in certain regions. Women continue to encounter various forms of gender inequality, such as stereotypes, marginalization, subordination, and the double burden. The practice of upholding justice is often marked by the inner conflict of the main character in defending her rights or fighting against injustice.